Faktor yang Mempengaruhi Jumlah Pengambilan Kredit di PD BPR Bank Pasar Kabupaten Jombang - Nurhayati, Wina; Hadi, Fadlan (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2023)
Credit distribution is the core function of rural banks in supporting regional economic activities. However, variations in the amount of credit taken by customers indicate the presence of complex determining factors. This study aims to analyze the factors influencing the amount of credit uptake at PD BPR Bank Pasar Jombang Regency. A quantitative explanatory approach was employed. Data were collected from internal bank reports and structured questionnaires distributed to productive and consumptive credit customers. The analyzed variables include loan interest rates, customer income, employment status, loan maturity, third party funds, non-performing loans, and service quality. Multiple linear regression was applied for data analysis. The results indicate that interest rates, employment status, and loan maturity significantly affect the amount of credit taken. Customer income shows no significant effect. These findings are consistent with previous studies by Nurhayati (2023), Widarno (2015), and Pranoto et al. (2019). The study provides practical implications for rural bank management in designing credit policies aligned with customer characteristics and internal bank conditions.